Miskonsepsi Mahasiswa pada Induksi Matematika Menggunakan Certainty of Response Index (CRI) - Khamida Siti Nur Atiqoh; Hafiz M (Jurnal Padegogik, 2021)
Misconception is something that can hinder the acceptance of new material and affect success in solving mathematical problems. This study aims to identify misconceptions in mathematics education students who are prospective mathematics teachers. Identifying and finding solutions to this misconception is very important because it can help improve student learning outcomes. The research method used is descriptive qualitative method using diagnostic tests and interviews. The diagnostic test was conducted on 28 mathematics education students using an instrument in the form of structured essay questions. Students are asked to answer questions with the right steps, then fill out a CRI questionnaire to measure the level of confidence in the answer. The results showed that there were half of all students who experienced misconceptions when doing proof by mathematical induction. There are 3 types of misconceptions experienced by students, namely: algebraic concept errors, misconceptions in the basic steps related to series, and algebraic calculation errors. The largest percentage are algebraic misconceptions.